Media Pembelajaran Digital dan Pemahaman Konsep IPA Siswa: Kajian Literatur Naratif atas Ragam, Potensi, dan Tantangan Implementasi - Hidayatullah, Firmansyah; Hayati, Nur; Hardyanti, Elvyana Tri Mei; Nabila, Irfiana Raisya; Yamin (PT. Komunitas Peneliti Alinea, 2026)
Digital learning media is increasingly used in science learning, but available studies still tend to discuss the effectiveness of each media separately. This article aims to analyze the variety of digital learning media, their pedagogical potential in supporting science concept understanding, and the challenges of implementing them in learning. This research uses a narrative literature review approach to 20 articles published between 2021 and 2025 and obtained through Google Scholar. Articles were selected based on their relevance to digital learning media, science learning, and students' conceptual understanding. Data were analyzed through thematic synthesis with the stages of reduction, grouping, comparison, and interpretation of findings. The results of the study indicate that the digital media used include interactive media, Augmented Reality, digital comics, interactive PowerPoint, Canva, Quizizz, gamification, App Inventor, Book Creator, and Solar System Scope. These media have the potential to support science concept understanding through visualization, interactivity, and increased student engagement. However, their effectiveness is influenced by teacher competence, content quality, infrastructure, and the suitability of the media to the characteristics of the material. This study contributes to mapping the variety, potential, and challenges of implementing digital learning media in an integrated manner.